Inherited anti-Jewish narratives in the current disinformation media. Case study from Slovakia - Hedviga Tkáčová (Revista Mediterránea de Comunicación)
This paper affords an insight into an important phenomenon related to the current worldwide increase in xenophobic behavior. In the past as well as in the present, the issue of anti-Semitism was the topic to be discussed; we note the dangers of the return and growth of populist and racist political parties and social movements while observing similar discussions today, especially in Eastern Europe (including Slovakia). They are linked to the current anti-vaccination and anti-war movements. This study had three objectives: (1) To present the critical anti-Semitic narratives that survived communism and were re-mediated after the establishment of an independent Slovakia in 1993; (2) to identify inherited mechanisms that continue to determine the forms of negative attitudes of Slovaks towards Jews; (3) to identify and analyze current narratives representing new forms of digital anti-Semitism in the current disinformation media in Slovakia. This paper employs a structured interview method with thirteen Slovak multi-disciplinary experts to research crucial inherited and current anti-Semitic narratives. Our research identified ten anti-Semitic narratives that remain in the current disinformation media. The research also points to two former mechanisms from the communist era that still influence the attitudes of Slovaks towards Jews.  This also influences the nature of contemporary anti-Semitism: the generational influence, under which intolerant attitudes pass from generation to generation, and the influence of (inherited) power and economic "remorse", accompanied by the common notion of the "exploitation" of countries (including Slovakia) by the Jewish community. Finally, four new and current narratives have been identified through structured interviews with experts, determining the nature of current digital anti-Semitism.